A meta-analysis of the effect of ultrasound activation parameters on phase-change nanodroplets in imaging and therapy - Dorvashi, Maryam; Harrison, Owen J.; Sultan, Hossam H.; Zhang, Ge; Thanou, Maya; Ghavami, Navid; Tiberi, Gianluigi; Ghavami, Mohammad; Harput, Sevan (Frontiers in Acoustics, 2024)
Phase-change nanodroplets (PCNDs) have been used in ultrasound imaging, targeted drug delivery, blood-brain-barrier (BBB) opening, sonothrombolysis and histotripsy for over a decade. For these ultrasound applications, PCNDs provide higher in vivo lifetime than microbubbles (MBs), the potential for extravasation inside tumour and on demand activation, which is the transition of the liquid-core of nanodroplets to gaseous microbubbles through acoustic droplet vaporisation (ADV). Operating above the ADV threshold can offer repeatable activation of PCNDs and the subsequent oscillation of acoustically activated PCNDs, which is advantageous in imaging and therapeutic applications. Efficient and repeatable activation of PCNDs require a good understanding of ultrasound parameters and nanodroplet composition for different biomedical applications. Therefore, this article presents a metaanalysis of the effect of ultrasound activation parameters on ADV for various PCNDs in different biomedical applications. About 7500 articles were considered for this study, but only 45 articles were chosen and evaluated in the meta-analysis based on the following criteria: (1) activation parameters, including ultrasound frequency, peak negative pressure, transmit pulse length or duration have been clearly mentioned, (2) droplets range in nanometre size (<1 µm), ( 3) experiments are performed at a temperature of 37°C and (4) ADV threshold has been clearly mentioned and observations are not due to inertial cavitation (IC). From selected publications, we recorded the activation frequency (0.06-16 MHz), ultrasound pressure (0.18-14.9 MPa), activation pulse length (µs-ms range) and nanodroplet size for different types of perfluorocarbon PCNDs (C3F8, C4F10, C5F12 and C6F14) and evaluated the relation of these parameters to each other. Finally, a Root Mean Square (RMS)-like power metric, which is a combination of ultrasound peak negative pressure and square root of ultrasound pulse length, is proposed for identifying the ADV threshold behaviour instead of using pressure or mechanical index values.